Differential Expression Profiles of lncRNA Following LPS-Induced Inflammation in Bovine Mammary Epithelial Cells - Wang, Jin-Peng; Hu, Qi-Chao; Yang, Jian; Luoreng, Zhuo-Ma; Wang, Xing-Ping; Ma, Yun; Wei, Da-Wei (Frontiers in Veterinary Science, 2021)
Bovine mastitis is an inflammatory response of mammary glands caused by pathogenic microorganisms such as Escherichia coli (E. coli). As a key virulence factor of E. coli, lipopolysaccharide (LPS) triggers innate immune responses via activation of the toll-like-receptor 4 (TLR4) signaling pathway. However, the molecular regulatory network of LPS-induced bovine mastitis has yet to be fully mapped. In this study, bovine mammary epithelial cells (bMECs) were exposed to LPS for 0, 6 and 12 hours to assess the expression profiles of long non-coding RNAs (lncRNAs) using RNA-seq. Differentially expressed lncRNAs (DElncRNAs) were filtered out of the raw data for subsequent analyses. A total of 2257 lncRNAs, including 210 annotated and 2047 novel lncRNAs were detected in all samples. A large proportion of lncRNAs were present in a high abundance, and 112 DElncRNAs were screened out at different time points. Compared with 0 hour of post-infection (hpi), there were 22 up- and 25 down-regulated lncRNAs in the 6 hpi group, and 27 up- and 22 down-regulated lncRNAs in the 12 hpi group. Compared with the 6 hpi group, 32 lncRNAs were up- and 25 lncRNAs were down-regulated in the 12 hpi group. These DElncRNAs may be involved in the regulation of a variety of immune-related processes including inflammatory responses bMECs exposed to LPS. Furthermore, two lncRNAs （TCONS_00039271 and TCONS_00139850） were identified that potentially function as key regulators cases of bovine mastitis caused by LPS or E. coli. This study lays a foundation for further research on molecular regulation of bovine mastitis, and also provides a reference for breeding strategies based on molecular markers for mastitis resistance in dairy cows.